Interfacial tensions of (H2O + H-2) and (H2O + CO2 + H-2) systems at temperatures of (298-448) K and pressures up to 45 MPa - Chow,YTF; Maitland,GC; Trusler,JPM (Fluid Phase Equilibria, 2018)
We report new interfacial tension (IFT) measurements of the (H2O + CO2 + H2) and (H2O + H2) systems at pressures of (0.5 to 45) MPa, and temperatures of (298.15 to 448.15) K, measured by the pendant-drop method. The expanded uncertainties at 95% confidence are 0.05K for temperature, 70kPa for pressure, 0.017·γ for IFT in the both the binary (H2O + H2) system and the ternary (CO2 + H2 + H2O) system. Generally, the IFT was found to decrease with both increasing pressure and increasing temperature. However, for (H2O + H2) at the lowest two temperatures investigated, the isothermal IFT data were found to exhibit a maximum as a function of pressure at low pressures before declining with increasing pressure. An empirical correlation has been developed for the IFT of the (H2O + H2) system in the full range of conditions investigated, with an average absolute deviation of 0.16mNm−1, and this is used to facilitate a comparison with literature values. Estimates of the IFT of the (H2O + CO2 + H2) ternary system, by an empirical combining rule based on the coexisting phase compositions and the interfacial tensions of the binary systems, were found to be unsuitable at low temperatures, with an average absolute deviation of 3.6mNm−1 over all the conditions investigated.